SAT0358 A ROLE FOR IL-4 AND IL-13 IN MODULATING THE IL-23/IL-17 AXIS IN ENTHESITIS. (2nd June 2020) - Bridgewood, C.; Sharif, K.; Rowe, H.; Russell, T.; Mcgonagle, D.
Abstract : Background: IL-4 and IL-13 are related Th2 cytokines, with documented roles in allergic inflammation such as atopic dermatitis (AD). Psoriatic Arthritis (PsA) is typically thought to be a result of Th1/Th17 driven response, and blockage of this pathway (IL-23, IL-17 and TNF) has proven successful. Despite this, there is a strong genetic risk association for IL-13 and PsA(1), however, the precise role of IL-13 in PsA is presently unknown. The enthesis is the region where tendons or ligaments attach to bone, and inflammation of this site (enthesitis) is thought to be the cardinal lesion of PsA, whereas as Rheumatoid Arthritis inflammation is more synovial centric. Dupilumab is a monoclonal antibody that works by blocking the common receptor chain (IL-4α) shared by both IL-13 and IL-4. Recent studies have reported that AD patients receiving dupilumab have developed clinical enthesitis(2). Objectives: To investigate whether IL-4 and IL-13 could modulate IL-23production from entheseal myeloid cells and IL-17 production from enthseal T-cells. Methods: Healthy enthesis samples from patients undergoing surgery for non-inflammatory conditions such a lumbar decompression or scoliosis were obtained. Enthesis samples were digested and stimulated (Fig 1A ) with LPS and anti-CD3 to induce IL-23 and IL-17 respectively. Samples were pre-treated with IL-4 and IL-13 to ascertain whether this modulated entheseal cytokine production. Results: Both IL-23 and IL-17 were readily induced from enthesis samples with IL-23 coming predominantly from entheseal myeloid resident cells (Fig 1B ) and IL-17A from T-cells (Fig 1C ). Pre-treatment of entheseal digested material with either IL-4 or IL-13 attenuated IL-23 secretion (Fig 1D ). Neither IL-4 nor IL-13 was able to significantly attenuate IL-17 secretion from enthesis T-cells, however IL-13 trended downwards and IL-4 surprisingly trended upwards (Fig 1E ). Conclusion: Our clinical and vitro data point towards a previously unknown role for IL-4 and IL-13 having a protective role in entheseal induction of IL23/17 axis cytokines. These findings point towards a novel explanation for IL-13 pathway SNPs in PsA and also a molecular explanation for why anti-IL4/13 therapy may induce entheseal pathology. References: [1]BOWES, J., S. EYRE, E. FLYNN, P. HO, S. SALAH, R.B. WARREN, H. MARZO-ORTEGA, L. COATES, R. MCMANUS, A.W. RYAN, D. KANE, E. KORENDOWYCH, N. MCHUGH, O. FITZGERALD, J. PACKHAM, A.W. MORGAN, C.E. GRIFFITHS, I.N. BRUCE, J. WORTHINGTON and A. BARTON. Evidence to support IL-13 as a risk locus for psoriatic arthritis but not psoriasis vulgaris. Ann Rheum Dis, 2011, 70 (6), pp.1016-9. [2]WILLSMORE, Z.N., R.T. WOOLF, C. HUGHES, B. MENON, B. KIRKHAM, C. SMITH and A. PINK. Development of inflammatory arthritis and enthesitis in patients on dupilumab: a case series. British Journal of Dermatology, 2019, 181 (5), pp.1068-1070. Disclosure of Interests: Charlie Bridgewood: None declared, Kassem Sharif: None declared, Hannah Rowe Grant/research support from: Novartis UK Investigator Initiated non-clinical research funding support, Tobias Russell Grant/research support from: Novartis UK Investigator Initiated non-clinical research funding support, Dennis McGonagle Grant/research support from: Janssen Research & Development, LLC